Four on the shore - Marshall, Edward; Marshall, James, 1942- (New York : Dial Books for Young Readers, 1985)
Hoping to scare away Spider's little brother, Willy, Lolly Spider, and Sam each tell a spooky story--but then Willy has a story of his own to tell.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
ALA Notable Books
2.0
K-3
Keywords: Ghosts -- Fiction; Ghosts -- Fiction